192k views
5 votes
14. Which of the following is equivalent to y

x? - 183 + 70 ?
y= (z – 9)2 – 11
y = (x + 9)2 +11
y= (2 – 9)2 +11
y= (1 + 9)2 – 11

User Mpmeyer
by
5.3k points

1 Answer

2 votes

Answer:

Explanation:

3x + 5y = 7

Since that is our original form, let's convert it so that we can find the slope:

5y = -3x + 7

y = -3/5 x + y

To get a perpendicular line, we need the negative reciprocal of the slope. This means that the sign switches and numerator and denominator flip:

m = 5/3

From here, we use the point-slope equation and then convert that into slope-intercept form:

y - y1 = m(x - x1)

y - 6 = 5/3(x - 0)

y - 6 = 5/3x

User The Coprolal
by
5.3k points